Enzyme‐linked immunosorbent assay by enhanced chemiluminescence detection for the standardization of estrogenic miroestrol in Pueraria candollei Graham ex Benth. (3rd November 2014) - Yusakul, Gorawit; Udomsin, Orapin; Tanaka, Hiroyuki; Morimoto, Satoshi; Juengwatanatrakul, Thaweesak; Putalun, Waraporn
Abstract Miroestrol (ME) is a potent phytoestrogen from the P. candollei tuberous root. It has been approved for use in clinical trials due to its beneficial effect on disorders associated with estrogen deficiency. To ensure medical efficacy and safety, high performance analytical methods for ME analysis are required to standardize products from the P. candollei root. An enhanced chemiluminescence enzyme‐linked immunosorbent assay (ECL‐ELISA) was developed and validated using a polyclonal antibody against ME and a chemiluminescent system of luminol–H2O2–horseradish peroxidase‐4‐(1‐imidazolyl) phenol. The ECL‐ELISA system exhibited linearity over a concentration range of 0.31–10.00 ng mL−1, for which the relative standard variation (%RSD) was less than 10% for both intra‐ and interplate determinations. The ECL‐ELISA is reliable for the determination of ME as reflected by the high recovery percentage (101.22–103.06%). As a comparative analysis, the ME content in each sample determined by ECL‐ELISA was correlated with high coefficients of determination with colorimetric ELISA (R2 = 0.998) and high performance liquid chromatography (HPLC) (R2 = 0.998) methods. The ECL‐ELISA method could be applied to all of the commercial products containing P. candollei root, when the products contain between 0.706 ± 0.046 and 13.123 ± 0.794 µg g−1 dry wt. of ME. This method is useful as a high performance analytical method for the quantity control of ME in raw materials and end products at both the research and industrial levels. Copyright © 2014 John Wiley & Sons, Ltd.